Anti-Caries Effect of a Mouthwash Containing Sambucus williamsii var. coreana Extract: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Yu-Rin Kim; Seoul-Hee Nam (MDPI AG, 2022)
This study was performed to verify the clinical effect of a mouthwash containing Sambucus williamsii var. coreana extract on the acid production of oral bacteria and bacteria involved in dental caries. A randomized, double-blind, and placebo-controlled trial was conducted on 66 patients of the following groups: a Sambucus williamsii var. coreana extract gargle group (n = 34) and a saline solution gargle group (n = 32). According to the application time of a mouthwash (before gargle application, immediately after gargle application, and five days after gargle application), we examined the emergence of dental caries-causing bacteria by PCR analysis and changes in the amount of acid production in dental plaque through a Cariview test. As a result of verifying the effect of inhibiting and preventing dental caries in the oral environment, the dental caries-causing bacteria decreased in the Sambucus williamsii var. coreana extract gargle group compared to the saline gargle group. In particular, Streptococcus mutans showed a marked decrease from immediately after application of gargle to 5 days after application. In addition, the mouthwash containing Sambucus williamsii var. coreana extract did not cause acid production and had low dental caries activity. A mouthwash containing Sambucus williamsii var. coreana extract, a natural substance, can be used as an anti-dental caries agent and be commercialized as an effective dental caries prevention agent that is safe for teeth and has an excellent antibacterial effect.